“We know that our voices are valued, and that people are actually going to listen”: co-producing an evaluation of a young people’s research advisory group - Louca-Mai Brady; Jacqueline Miller; Eleri McFarlane-Rose; Jasmine Noor; Rhianne Noor; Annegret Dahlmann-Noor (Research Involvement and Engagement, 2023)
Plain English summary Children and young people (CYP) have a right to be involved in things that affect them, including research. There is growing interest in children and young people’s involvement in health research in the United Kingdom (UK), as well as understanding that what works for CYP is often different to what works for adults. This paper presents an evaluation of the Young Person's Advisory Group (YPAG) at Moorfields Eye Hospital in London. Evaluation uses research methods to find out how well a service or project is working and meeting the needs of those who use it, and how to improve things that could be better. A group of young evaluators, supported by adult researchers, designed and ran the evaluation; three of the young evaluators also helped write this paper. In our evaluation we used focus (discussion) groups and online surveys with young group members, their parents and carers, researchers who had worked with the group, the group’s facilitators (adults who help manage the group) and funders. We found that group members valued the social and creative aspects of the group as well as learning about research and developing skills and confidence. Learning was a two-way process, with both researchers and facilitators talking about how much they had learnt from working with the YPAG. All participants talked about the importance of feeling that CYP are making a difference to research, as well as of CYP’s right to be involved. Planning and support were important to the group working well, but we found that having the money and time to do this well was not always easy. And, while lots of researchers were keen to work with the group, and talked about how this had helped their research, we need to do more to engage researchers who have yet to be convinced. We also found that, while we wanted to ‘co-produce’ the group and share power for all big decisions, this was something we had to work towards, especially when group members were young and/or new to research and involvement. Co-producing an evaluation helped us to learn about the benefits and challenges of involving CYP in research, as well as how to involve them in evaluating that involvement.